2014
DOI: 10.1186/1471-2407-14-276
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of MMPs by E2F1, Sp1 and NF-kappa B controls the small cell lung cancer invasive phenotype

Abstract: BackgroundE2F1 transcription factor plays a vital role in the regulation of diverse cellular processes including cell proliferation, apoptosis, invasion and metastasis. E2F1 overexpression has been demonstrated in small cell lung cancer (SCLC), and extensive metastasis in early phase is the most important feature of SCLC. In this study, we investigated the involvement of E2F1 in the process of invasion and metastasis in SCLC by regulating the expression of matrix metalloproteinases (MMPs).MethodsImmunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 41 publications
3
55
1
Order By: Relevance
“…We also observed that E2F1 increased Bcl-2, cyclin D1, survivin, MMP2, and MMP9 expression in ovarian carcinoma, but did not alter p53 expression. These results are similar to the oncogenic role of E2F1 in small cell lung cancer [28] and clear cell renal cell carcinoma [29], but differ from the suppressive effect of E2F1 in gastric cancer [1719] and Hodgkin lymphoma [25]. Our findings suggest that E2F1 functions as an oncogene in ovarian carcinoma in part by upregulating Bcl-2, cyclin D1, survivin, MMP2, and MMP9 expression.…”
Section: Discussionsupporting
confidence: 79%
“…We also observed that E2F1 increased Bcl-2, cyclin D1, survivin, MMP2, and MMP9 expression in ovarian carcinoma, but did not alter p53 expression. These results are similar to the oncogenic role of E2F1 in small cell lung cancer [28] and clear cell renal cell carcinoma [29], but differ from the suppressive effect of E2F1 in gastric cancer [1719] and Hodgkin lymphoma [25]. Our findings suggest that E2F1 functions as an oncogene in ovarian carcinoma in part by upregulating Bcl-2, cyclin D1, survivin, MMP2, and MMP9 expression.…”
Section: Discussionsupporting
confidence: 79%
“…We previously found that Sp1 mediates the antifibrotic effects of miR‐7a/b in angiotensin II–stimulated cardiac fibroblasts by targeting collagen I . Meanwhile, the MMP‐9 expression level was shown to be transcriptionally regulated by Sp1 . MMP‐9 plays a crucial role in elastin degradation, which is highly pro‐calcific.…”
Section: Discussionmentioning
confidence: 99%
“…Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014). Most of such studies focused on cancer cells in which silencing of selected MMP expression resulted in the inhibition of the cell migration and invasion to other tissues (Sun et al, 2008;Tsung et al, 2008;Shen et al, 2012;Tang et al, 2013;Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%